2009
DOI: 10.4049/jimmunol.0901337
|View full text |Cite
|
Sign up to set email alerts
|

A cis-Acting Regulatory Variant in the IL2RA Locus

Abstract: The mechanism for the association of type 1 diabetes (T1D) with IL2RA remains to be clarified. Neither of the two distinct, transmission-disequilibrium confirmed loci mapping to this gene can be explained by a coding variant. An effect on the levels of the soluble protein product sIL-2RA has been reported but its cause and relationship to disease risk is not clear. To look for an allelic effect on IL2RA transcription in cis, we examined RNA from 48 heterozygous lymphocyte samples for differential allele expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…These data contradict previous studies that have suggested that a haplotype, best marked by rs3118470 increases T1D risk through diminished expression of the IL-2R. 19 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These data contradict previous studies that have suggested that a haplotype, best marked by rs3118470 increases T1D risk through diminished expression of the IL-2R. 19 …”
Section: Discussioncontrasting
confidence: 99%
“…The rs3118470 SNP has also been associated with differential allele expression of IL2RA messenger RNA. 19 …”
Section: Introductionmentioning
confidence: 99%
“…These occur in both CD25 hi T cells and memory Teff cells and include decreased IL2RA RNA and CD25 surface expression in Treg (confirmed in Figure S2) and memory Teff [25], [32], [34], increased frequency of CD25 + naive T cells [25], decreased response to IL-2 [32] and increased serum sIL-2RA [16], [24]. In contrast, the IL2RA rs2104286 risk haplotype, associated with both T1D and MS, only shares a subset of these phenotypes, including increased frequency of CD25 + naïve T cells and increased serum sIL-2RA.…”
Section: Discussionmentioning
confidence: 70%
“…This could indicate a defect in the cellular subset that is the source of cleaved IL2R␣. An alternative explanation may be that, even in the presence of normal Treg frequencies in T1D (70), IL2RA polymorphisms account for functional defects in the Treg compartment (72,346). In conclusion, it seems that although genetic variability in the IL2RA gene is associated with several autoimmune diseases including T1D, the mechanisms and extent to which sIL2R␣ levels mediate these conditions differs significantly.…”
Section: E Il2ramentioning
confidence: 74%